A polymer positive electrode material and its preparation method and application

By introducing multivariate nitrogen heterocyclic rings and oxidants into the sulfurized polymer positive electrode material, it improves its electron absorption capacity, solves the problem of low voltage platform of existing sulfur positive electrode material, and realizes the energy density of lithium sulfur batteries Significantly improved.

CN118930690BActive Publication Date: 2024-12-27SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411405026.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-27
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The voltage platform of existing sulfur cathode materials is low, resulting in insufficient energy density of lithium sulfur batteries, and traditional modification methods such as ion doping and conductive compound polymerization are difficult to effectively improve the voltage platform.

Method used

The polymer containing multivariate nitrogen heterocyclic ring is used to oxidize and react with an oxidizing agent to generate nitrogen oxide groups, and the electron absorption capacity of the polymer positive electrode material is enhanced through the conjugation effect, and the sulfurized polymer positive electrode material is prepared through the sulfurization reaction to increase its voltage. platform.

Benefits of technology

The voltage platform of the vulcanized polymer cathode material has been successfully improved, making it exceed 2V, significantly increasing the energy density of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a polymer positive electrode material and a preparation method and application thereof. The method comprises the following steps: firstly subjecting a polymer containing a polynary nitrogen heterocycle, an oxidant and a solvent to an oxidation reaction to obtain a nitrogen oxide of the polymer containing a polynary nitrogen heterocycle; and then subjecting the obtained nitrogen oxide of the polymer containing a polynary nitrogen heterocycle to a sulfur material for a sulfurization reaction to obtain the polymer positive electrode material. The present invention provides a method for preparing a sulfurized polymer positive electrode material with low cost, mild process conditions and easy industrialization, thereby improving the voltage platform of the sulfurized polymer positive electrode material to more than 2V, thereby improving the energy density of the lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to a polymer positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, sulfur cathode materials have attracted extensive attention due to their abundant resources and low price, and they can also ensure the high energy density of lithium-sulfur batteries. However, traditional carbon / sulfur (C / S) composites usually exhibit poor electrochemical activity due to the insulating properties of sulfur and the Li 2 This is due to the solubility of S. In order to achieve efficient S-Li 2 S conversion requires a solid-liquid-solid path, but this brings serious problems (including severe polysulfide cross-contamination, reduced conductivity and increased viscosity caused by polysulfide production, etc.). In order to overcome these problems, various alternative sulfur-based materials have been proposed, one of which is sulfurized polyacrylonitrile (SPAN). The sulfur-based active substances in SPAN are covalently bonded to the nitrogen-containing conductive framework, giving it obvious electrochemical advantages: the strong bond with the polymer framework can provide better protection for sulfur, preventing it from dissolving and side reactions with the electrolyte, while maintaining the dispersion of sulfur at the molecular level, thereby ensuring that SPAN has sufficient electrochemical activity and avoiding the adverse effects of polysulfides.

[0003] As we all know, battery energy density is an important parameter to measure battery performance. Its corresponding value is closely positively correlated with the voltage platform of the positive electrode material, that is, the higher the voltage platform of the positive electrode material, the higher the energy density of the battery. The voltage platform of the positive electrode material is related to its own chemical system. At present, the voltage platform of SPAN material is about 1.8V, which needs to be further modified and improved.

[0004] Most of the existing technologies focus on improving the capacity of SPAN, such as modifying the positive electrode material by ion doping or conductive compound polymerization, but few people have reported on the technical means of improving the voltage platform of SPAN materials. In addition, improving the voltage platform of SPAN is very complicated because it involves multiple aspects such as the electronic structure of the material, the electrochemical reaction mechanism, and the interaction with the electrolyte.

[0005] Therefore, in the art, there is an urgent need to develop a method for increasing the voltage platform of polymer cathode materials such as SPAN. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a polymer positive electrode material and a preparation method and application thereof. The present invention provides a preparation method of a vulcanized polymer positive electrode material with low cost, mild process conditions and easy industrialization, thereby improving the voltage platform of the vulcanized polymer positive electrode material to exceed 2V, thereby improving the energy density of lithium-sulfur batteries.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a polymer positive electrode material, the method comprising the following steps:

[0009] S1. A polymer comprising a polycyclic nitrogen heterocycle, an oxidant and a solvent are subjected to an oxidation reaction to obtain a nitrogen oxide of the polymer comprising a polycyclic nitrogen heterocycle;

[0010] S2. Performing a sulfurization reaction on the nitrogen oxide of the polymer containing polycyclic nitrogen obtained in step S1 and a sulfur material to obtain the polymer positive electrode material.

[0011] On the one hand, the present invention adopts a polymer containing a polycyclic nitrogen ring as a modification object, because the main chain structure of the polymer containing a polycyclic nitrogen ring has a high degree of conjugation, and at the same time reduces the content of the defective structure six-membered ring, thereby improving the specific capacity and cycle stability of the finally prepared polymer positive electrode material; on the other hand, the present invention converts the nitrogen oxygen on part of the polycyclic ring into a nitrogen oxide group (-NO) through an oxidant. Since the electronegativity of oxygen is greater than that of nitrogen, an electron-withdrawing conjugation effect can occur, thereby improving the electron-withdrawing ability of the overall polymer positive electrode material, so that the reduction voltage of the polymer positive electrode material can be increased, and lithium insertion reaction is more likely to occur, thereby improving the energy density of the lithium-sulfur battery.

[0012] Preferably, the polymer containing a polycyclic nitrogen ring in step S1 includes at least one of cyclized polyacrylonitrile, cyclized polyimidazole or cyclized polypyridine.

[0013] Preferably, the oxidant in step S1 comprises hydrogen peroxide.

[0014] Preferably, the step S1 further comprises adding an acidity regulator before the oxidation reaction.

[0015] In the present invention, the acidity regulator includes glacial acetic acid.

[0016] Preferably, the mass ratio of the polymer containing polycyclic nitrogen heterocycles, the oxidant and the acidity regulator is (1-10): (1-60): (20-100), preferably (2-8): (2-40): (30-70), for example, it can be 1: 1: 20, 2: 1: 25, 1: 2: 25, 3: 1: 28, 2: 2: 30, 4: 5: 35, 5: 8: 40, 6: 10: 45, 7: 20: 50, 8: 30: 55, 6: 35: 60, 7: 40: 70, 10: 50: 80, 9: 60: 90, 10: 60: 100, etc. The present invention enhances the electron-withdrawing ability of the polymer positive electrode material and improves the reduction potential for lithium insertion by regulating the mass ratio of the polymer containing polycyclic nitrogen heterocycles, the oxidant and the acidity regulator to a suitable range.

[0017] Preferably, the oxidation reaction process in step S1 includes first subjecting the polymer containing polycyclic nitrogen heterocycles, a portion of an oxidant, an acidity regulator and a solvent to a first oxidation reaction, and then adding another portion of an oxidant to conduct a second oxidation reaction to obtain the nitrogen oxide of the polymer containing polycyclic nitrogen heterocycles.

[0018] Preferably, the mass ratio of the part of the oxidant to the other part of the oxidant is (1-5):(1-5), preferably 1:1, for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 2:1, 3:1, 4:1, 5:1, 2:3, 1:1, 4:3, 4:5, 5:4, etc.

[0019] Preferably, the solvent comprises water.

[0020] Preferably, the temperature of the first oxidation reaction is 65°C-80°C, for example, 65°C, 68°C, 70°C, 75°C, 80°C, etc.; the time is 2h-8h, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc.

[0021] Preferably, the temperature of the second oxidation reaction is 65°C-80°C, for example, 65°C, 68°C, 70°C, 75°C, 80°C, etc.; the time is 10h-20h, for example, 10h, 12h, 15h, 18h, 20h, etc.

[0022] In the present invention, by regulating the steps and parameters of the two oxidation reactions, the polycyclic nitrogen ring undergoes sufficient nitrogen-oxidation reaction, so that the reaction degree is complete.

[0023] Preferably, the second oxidation reaction includes a purification process after completion.

[0024] In the present invention, the purification treatment includes vacuum distillation and neutral treatment in sequence. The vacuum distillation treatment includes vacuum distilling the reaction product at 55°C until no liquid flows out; the neutral treatment includes adding potassium bicarbonate solution to the distilled product to neutralize it, washing it with water and ethanol for multiple times, and then vacuum drying it.

[0025] In the present invention, the method for preparing the polymer containing polycyclic nitrogen rings in step S1 comprises the following steps: heat-treating the nitrogen-containing polymer under aerobic conditions to obtain the polymer containing polycyclic nitrogen rings.

[0026] In the present invention, the nitrogen-containing polymer includes at least one of polyacrylonitrile, polyimidazole or polypyridine.

[0027] In the present invention, the heat treatment temperature is 180°C-220°C, for example, it can be 180°C, 190°C, 200°C, 210°C, 220°C, etc.; the time is 1h-5h, for example, it can be 1h, 2h, 3h, 4h, 5h, etc.

[0028] Preferably, the step S2 further includes adding a vulcanization accelerator before the vulcanization reaction.

[0029] In the present invention, the vulcanization accelerator includes a guanidine accelerator to increase the sulfur content of the polymer.

[0030] Preferably, the mass ratio of the nitrogen oxide containing the polynary nitrogen heterocyclic polymer, the sulfur material and the vulcanization accelerator is 1:(1-10):(0.01-0.3), preferably 1:(2-6):(0.01-0.1), for example, it can be 1:2:0.01, 1:2.2:0.02, 1:2.5:0.03, 1:2.8:0.04, 1:3:0.05, 1:3.2:0.06, 1: 3.5:0.07, 1:3.8:0.08, 1:4:0.09, 1:4.2:0.1, 1:4.5:0.03, 1:4.8:0.05, 1:5:0.06, 1:5.2:0.07, 1:5.5:0.08, 1:5.8:0.09, 1:6:0.1, 1:7:0.15, 1:8:0.2, 1:9:0.25, 1:10:0.3, etc.

[0031] Preferably, the vulcanization reaction process in step S2 comprises sequentially grinding and calcining the nitrogen oxide of the polymer containing polycyclic nitrogen, the sulfur material and the vulcanization accelerator obtained in step S1.

[0032] Preferably, the calcination treatment is performed under an inert atmosphere.

[0033] Preferably, the calcination treatment temperature is 300°C-350°C, for example, it can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, etc.; the calcination time is 2h-10h, for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.

[0034] In a second aspect, the present invention provides a polymer positive electrode material, wherein the polymer positive electrode material is prepared by the method for preparing a polymer positive electrode material according to the first aspect.

[0035] In a third aspect, the present invention provides a positive electrode, wherein the positive electrode comprises a positive electrode active material, wherein the positive electrode active material comprises the polymer positive electrode material according to the second aspect.

[0036] In a fourth aspect, the present invention provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode according to the third aspect.

[0037] The discharge voltage platform of the positive electrode prepared by the present invention using the polymer positive electrode material according to the second aspect is not less than 2V, thereby greatly improving the energy density of the assembled lithium-sulfur battery.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present invention provides a method for preparing a polymer positive electrode material. On the one hand, the present invention adopts a polymer containing a polycyclic nitrogen heterocycle as a modification object. This is because the main chain structure of the polymer containing a polycyclic nitrogen heterocycle has a high degree of conjugation, and at the same time reduces the content of the defective structure hexacyclic ring, thereby improving the specific capacity and cycle stability of the finally prepared polymer positive electrode material; on the other hand, the present invention converts nitrogen oxides on part of the polycyclic rings into nitrogen oxide groups (-NO) by an oxidant. Since the electronegativity of oxygen is greater than that of nitrogen, an electron-withdrawing conjugation effect can occur, thereby improving the electron-withdrawing ability of the overall polymer positive electrode material, so that the reduction voltage of the polymer positive electrode material can be increased, and lithium insertion reaction is more likely to occur, thereby improving the energy density of the lithium-sulfur battery. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0041] Example 1

[0042] This embodiment provides a sulfurized polyacrylonitrile nitrogen oxide positive electrode material and a preparation method thereof, which comprises the following steps:

[0043] S1. The polyacrylonitrile powder was heated to 200°C in an air atmosphere for 2h and then naturally cooled to room temperature to obtain a cyclized polyacrylonitrile powder;

[0044] A mixture of glacial acetic acid, 50% aqueous hydrogen peroxide solution (mass fraction of 30%) and 5g of cyclized polyacrylonitrile was heated in a water bath to 70°C, reacted for 3 hours, and then the remaining 50% aqueous hydrogen peroxide solution (mass fraction of 30%) was added, and the reaction was continued for 10 hours, wherein the mass ratio of cyclized polyacrylonitrile, hydrogen peroxide and glacial acetic acid was 1:4:10. The reaction product was distilled under reduced pressure at 55°C until no liquid flowed out, potassium bicarbonate solution was added to neutralize it to neutrality, and it was washed with water and ethanol for several times, and vacuum dried to obtain the nitrogen oxide of polyacrylonitrile;

[0045] S2. The polyacrylonitrile nitrogen oxide, sulfur material and diphenylguanidine vulcanization accelerator obtained in step S1 are mixed uniformly by ball milling in a mass ratio of 1:3:0.05 to obtain a mixed powder. The mixed powder is placed in a closed reactor, an argon atmosphere is introduced, and heat-treated at 320° C. for 4 hours, and then naturally cooled to obtain the sulfurized polyacrylonitrile nitrogen oxide positive electrode material.

[0046] Example 2

[0047] This embodiment provides a sulfurized polyacrylonitrile nitrogen oxide positive electrode material and a preparation method thereof, which comprises the following steps:

[0048] S1. The polyacrylonitrile powder was heated to 200°C in an air atmosphere for 2h and then naturally cooled to room temperature to obtain a cyclized polyacrylonitrile powder;

[0049] A mixture of glacial acetic acid, 60% aqueous hydrogen peroxide solution (mass fraction 30%) and 5g of cyclized polyacrylonitrile was heated to 80°C in a water bath, reacted for 3 hours, and then 40% aqueous hydrogen peroxide solution (mass fraction 30%) was added, and the reaction was continued for 10 hours, wherein the mass ratio of cyclized polyacrylonitrile, hydrogen peroxide and glacial acetic acid was 1:1:15. The reaction product was distilled under reduced pressure at 55°C until no liquid flowed out, potassium bicarbonate solution was added to neutralize it to neutrality, and it was washed with water and ethanol for several times, and vacuum dried to obtain the nitrogen oxide of polyacrylonitrile;

[0050] S2. The polyacrylonitrile nitrogen oxide, sulfur material and diphenylguanidine vulcanization accelerator obtained in step S1 are mixed uniformly by ball milling in a mass ratio of 1:2:0.01 to obtain a mixed powder. The mixed powder is placed in a closed reactor, an argon atmosphere is introduced, and heat-treated at 320° C. for 4 hours, and then naturally cooled to obtain the sulfurized polyacrylonitrile nitrogen oxide positive electrode material.

[0051] Example 3

[0052] This embodiment provides a sulfurized polyacrylonitrile nitrogen oxide positive electrode material and a preparation method thereof, which comprises the following steps:

[0053] S1. The polyacrylonitrile powder was heated to 200°C in an air atmosphere for 2h and then naturally cooled to room temperature to obtain a cyclized polyacrylonitrile powder;

[0054] A mixture of glacial acetic acid, 50% aqueous hydrogen peroxide solution (mass fraction 30%) and 5g of cyclized polyacrylonitrile was heated in a water bath to 65°C, reacted for 3 hours, and then 50% aqueous hydrogen peroxide solution (mass fraction 30%) was added, and the reaction was continued for 10 hours, wherein the mass ratio of cyclized polyacrylonitrile, hydrogen peroxide and glacial acetic acid was 1:5:8.75. The reaction product was distilled under reduced pressure at 55°C until no liquid flowed out, potassium bicarbonate solution was added to neutralize it to neutrality, and it was washed with water and ethanol for several times, and vacuum dried to obtain the nitrogen oxide of polyacrylonitrile;

[0055] S2. The polyacrylonitrile nitrogen oxide, sulfur material and diphenylguanidine vulcanization accelerator obtained in step S1 are mixed uniformly by ball milling in a mass ratio of 1:6:0.1 to obtain a mixed powder. The mixed powder is placed in a closed reactor, an argon atmosphere is introduced, and heat-treated at 320° C. for 4 hours, and then naturally cooled to obtain the sulfurized polyacrylonitrile nitrogen oxide positive electrode material.

[0056] Example 4

[0057] This embodiment provides a sulfurized polyacrylonitrile nitrogen oxide positive electrode material and a preparation method thereof, which comprises the following steps:

[0058] S1. The polyacrylonitrile powder was heated to 180°C in an air atmosphere for 2 hours and cooled naturally to room temperature to obtain a cyclized polyacrylonitrile powder;

[0059] A mixture of glacial acetic acid, 80% aqueous hydrogen peroxide solution (mass fraction of 30%) and 5g of cyclized polyacrylonitrile was heated in a water bath to 70°C, reacted for 3 hours, and then 20% aqueous hydrogen peroxide solution (mass fraction of 30%) was added, and the reaction was continued for 15 hours, wherein the mass ratio of cyclized polyacrylonitrile, hydrogen peroxide and glacial acetic acid was 1:1:20. The reaction product was distilled under reduced pressure at 55°C until no liquid flowed out, potassium bicarbonate solution was added to neutralize it to neutrality, and it was washed with water and ethanol for several times, and vacuum dried to obtain the nitrogen oxide of polyacrylonitrile;

[0060] S2. The polyacrylonitrile nitrogen oxide, sulfur material and diphenylguanidine vulcanization accelerator obtained in step S1 are mixed uniformly by ball milling in a mass ratio of 1:1:0.01 to obtain a mixed powder. The mixed powder is placed in a closed reactor, an argon atmosphere is introduced, and heat-treated at 300° C. for 4 hours, and then naturally cooled to obtain the sulfurized polyacrylonitrile nitrogen oxide positive electrode material.

[0061] Example 5

[0062] This embodiment provides a sulfurized polyacrylonitrile nitrogen oxide positive electrode material and a preparation method thereof, which comprises the following steps:

[0063] S1. The polyacrylonitrile powder was heated to 220°C in an air atmosphere for 2h and cooled naturally to room temperature to obtain a cyclized polyacrylonitrile powder;

[0064] A mixture of glacial acetic acid, 80% aqueous hydrogen peroxide solution (mass fraction 30%) and 5g of cyclized polyacrylonitrile was heated to 70°C in a water bath, reacted for 3 hours, and then 20% aqueous hydrogen peroxide solution (mass fraction 30%) was added, and the reaction was continued for 15 hours, wherein the mass ratio of cyclized polyacrylonitrile, hydrogen peroxide and glacial acetic acid was 1:6:10. The reaction product was distilled under reduced pressure at 55°C until no liquid flowed out, potassium bicarbonate solution was added to neutralize it to neutrality, and it was washed with water and ethanol for several times, and vacuum dried to obtain the nitrogen oxide of polyacrylonitrile;

[0065] S2. The polyacrylonitrile nitrogen oxide, sulfur material and diphenylguanidine vulcanization accelerator obtained in step S1 are mixed uniformly by ball milling in a mass ratio of 1:10:0.3 to obtain a mixed powder. The mixed powder is placed in a closed reactor, an argon atmosphere is introduced, and heat-treated at 350° C. for 4 hours, and then naturally cooled to obtain the sulfurized polyacrylonitrile nitrogen oxide positive electrode material.

[0066] Example 6

[0067] The difference between this embodiment and embodiment 1 is that in step S1, polyacrylonitrile is replaced by polypyridine of the same content, and the rest is the same as embodiment 1.

[0068] Example 7

[0069] The difference between this embodiment and embodiment 1 is that in step S1, the mass ratio of cyclized polyacrylonitrile, hydrogen peroxide and glacial acetic acid is 1:0.6:12, and the rest is the same as embodiment 1.

[0070] Example 8

[0071] The difference between this embodiment and embodiment 1 is that in step S1, the mass ratio of cyclized polyacrylonitrile, hydrogen peroxide and glacial acetic acid is 1:6:5, and the rest is the same as embodiment 1.

[0072] Example 9

[0073] The difference between this embodiment and embodiment 1 is that the temperature of the first oxidation reaction and the second oxidation reaction in step S1 are both 55° C., and the rest is the same as embodiment 1.

[0074] Example 10

[0075] The difference between this embodiment and embodiment 1 is that no diphenylguanidine vulcanization accelerator is added in step S2, and the rest is the same as embodiment 1.

[0076] Comparative Example 1

[0077] The difference between this comparative example and Example 1 is that the preparation method comprises the following steps:

[0078] S1. The polyacrylonitrile powder was heated to 200°C in an air atmosphere for 2h and then naturally cooled to room temperature to obtain a cyclized polyacrylonitrile powder;

[0079] S2. The cyclized polyacrylonitrile powder, sulfur material and diphenylguanidine vulcanization accelerator obtained in step S1 were mixed uniformly by ball milling in a mass ratio of 1:3:0.05 to obtain a mixed powder. The mixed powder was placed in a closed reactor, an argon atmosphere was introduced, and heat-treated at 320°C for 4 hours and then naturally cooled to obtain a sulfurized cyclized polyacrylonitrile positive electrode material. The rest was the same as in Example 1.

[0080] Comparative Example 2

[0081] The difference between this comparative example and Example 1 is that the preparation method comprises the following steps:

[0082] Polyacrylonitrile powder, sulfur material and diphenylguanidine vulcanization accelerator were mixed uniformly by ball milling in a mass ratio of 1:3:0.05 to obtain a mixed powder. The mixed powder was placed in a closed reactor, introduced into an argon atmosphere, and heat treated at 320° C. for 4 hours and then naturally cooled to obtain a sulfurized polyacrylonitrile positive electrode material. The rest was the same as in Example 1.

[0083] Test conditions

[0084] The vulcanized polymer positive electrode materials provided in Examples 1 to 10 and Comparative Examples 1 to 2 were tested, and the test method was as follows:

[0085] The vulcanized polymer positive electrode materials prepared in Examples 1-10 and Comparative Examples 1-2 were used as positive electrode active materials, and positive electrode slurry was prepared according to the mass ratio of positive electrode active material: conductive carbon black: binder LA133 of 80:13:7. The fully embedded lithium graphite material was used as the negative electrode, and the concentration of LiPF 6 +EC / EMC / DMC (volume ratio of 1:1:1) was used as the electrolyte, and polypropylene film was used as the separator. The single-chip soft-pack battery was assembled in a glove box, where H 2 O and O 2 The content is less than 0.1ppm.

[0086] Use a balance to measure the total mass of the battery, then place the battery in a battery testing cabinet to test the charge and discharge performance. The charge and discharge rate is 0.3C, and the voltage range is 0.01-3.00V. Record the battery's second discharge capacity and voltage, and calculate the battery's energy density. The calculation formula is as follows:

[0087] Energy density = (battery discharge capacity × voltage / battery mass).

[0088] The test results are shown in Table 1:

[0089] Table 1

[0090]

[0091] It can be seen from Table 1 that, compared with Comparative Examples 1-2, under appropriate experimental conditions (Examples 1-6), a nitrogen oxidation reaction occurs on the polycyclic heterocycle of the polymer material provided by the present invention, thereby introducing a nitroxide group with a stronger electronegativity, which is beneficial to enhancing the electron-withdrawing ability of the overall polymer positive electrode material, making it easy to undergo a lithium insertion reduction reaction at a relatively high potential, and ultimately improving the energy density of the lithium-sulfur battery.

[0092] Compared with Example 1, Examples 7-9 show that when the ratio of the polymer containing a polycyclic nitrogen heterocycle, the hydrogen peroxide oxidation agent and the glacial acetic acid regulator is not within the preferred range of the present invention, or the reaction temperature is not within the preferred range of the present invention, it will affect the nitrogen oxidation effect of the prepared polymer positive electrode material, thereby affecting the electron-withdrawing ability and lithium storage performance of the polymer positive electrode material.

[0093] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a polymer positive electrode material, characterized in that: The method comprises the following steps: S1. A polymer comprising a polycyclic nitrogen heterocycle, an oxidant and a solvent are subjected to an oxidation reaction to obtain a nitrogen oxide of the polymer comprising a polycyclic nitrogen heterocycle; S2. The nitrogen oxide of the polymer containing a polycyclic nitrogen ring obtained in step S1 and the sulfur material are subjected to a sulfurization reaction to obtain the polymer positive electrode material; The polymer containing polycyclic nitrogen rings in step S1 includes cyclized polyacrylonitrile; The step S1 further includes adding an acidity regulator before the oxidation reaction; The mass ratio of the polymer containing polycyclic nitrogen heterocycles, the oxidant and the acidity regulator is (1-10):(1-60):(20-100); The oxidation reaction process in step S1 includes firstly subjecting the polymer containing polycyclic nitrogen heterocycles, a portion of an oxidant, an acidity regulator and a solvent to a first oxidation reaction, and then adding another portion of an oxidant to conduct a second oxidation reaction to obtain the nitrogen oxide of the polymer containing polycyclic nitrogen heterocycles; The temperature of the first oxidation reaction is 65°C-80°C; The temperature of the second oxidation reaction is 65°C-80°C.

2. The method according to claim 1, characterized in that: The oxidant in step S1 includes hydrogen peroxide.

3. The method according to claim 1, characterized in that The mass ratio of the one part of the oxidant to the other part of the oxidant is (1-5):(1-5); The solvent includes water; The time of the first oxidation reaction is 2h-8h; The second oxidation reaction time is 10h-20h; The second oxidation reaction includes purification treatment after completion.

4. The method according to claim 1, characterized in that: The step S2 also includes adding a vulcanization accelerator before the vulcanization reaction; The mass ratio of the nitrogen oxide, the sulfur material and the vulcanization accelerator of the polymer containing polynary nitrogen heterocycles is 1:(1-10):(0.01-0.3).

5. The method according to claim 4, characterized in that The process of the vulcanization reaction in step S2 comprises grinding and calcining the nitrogen oxide of the polymer containing polycyclic nitrogen, the sulfur material and the vulcanization accelerator obtained in step S1 in sequence; The calcination treatment is carried out under an inert atmosphere; The calcination treatment is carried out at a temperature of 300° C.-350° C. and for a time of 2 h-10 h.

6. A polymer positive electrode material, characterized in that: The polymer positive electrode material is prepared by the method for preparing a polymer positive electrode material according to any one of claims 1-5.

7. A positive electrode, characterized in that The positive electrode includes a positive electrode active material, and the positive electrode active material includes the polymer positive electrode material according to claim 6.

8. A lithium-sulfur battery, characterized in that: The lithium-sulfur battery comprises a positive electrode, a negative electrode and an electrolyte, and the positive electrode comprises the positive electrode according to claim 7.